Urban Street Concept Based on The Quran Perspective: The Most Comprehensive Solution to Street Problems - Muhammad Imam Faqihuddin; Aldrin Yusuf Firmansyah (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2023)
Streets are fundamental in the urban realm and always have specific problems. Many street concepts are believed to be able to solve the issues only partially. Therefore, they should work together to solve them comprehensively. Based on this case, to ensure their comprehensiveness, this research aims to offer Quran as an undebatable inspiration in finding new ideas for urban street concepts and filling the holes to solve those complicated problems. By using the content analysis method, this research analyzes eight street concepts: Those are livable, sustainable, walkable, biophilic, complete, democratic, user-friendly, and Quranic street, which is based on Quran to identify the indicators for each of them. The result showed that new inspirations of urban street concepts were found. They could be considered as new indicators of urban street concepts, which can provide a more comprehensive solution to the complicated street problems.